2015
DOI: 10.3923/ijp.2015.496.501
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Susceptibility of Clinical Aspergillus Species to Some Antifungal Agents

Abstract: Aspergillus species are regularly involved in human broncho-pulmonary diseases, mainly in immunocompromised patients. The essential oils extracted from three different plants were tested for their inhibitory effect on the growth of five pathogenic Aspergilli including Aspergillus flavus, Aspergillus fumigatus, Aspergillus niger, Aspergillus versicolor and Aspergillus terreus which are pathogens with clinical importance. The results of the antimicrobial tests showed that the isolated essential oils inhibited th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Aspergillosis comprises various diseases produced by the members of the Aspergillus genus such as A. flavus , A. fumigatus , A. niger , and A. terreus that are the common species accountable for infections ( Bahkali et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aspergillosis comprises various diseases produced by the members of the Aspergillus genus such as A. flavus , A. fumigatus , A. niger , and A. terreus that are the common species accountable for infections ( Bahkali et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Aspergillosis comprises various diseases produced by the members of the Aspergillus genus such as A. flavus, A. fumigatus, A. niger, and A. terreus that are the common species accountable for infections (Bahkali et al, 2015). Bahkali et al (2015) reported that O. basilicum (20 mg/ml for 7 days) generally prevented the hyphae growth and spore germination of A. fumigatus and A. terreus. Also, this extract exhibited a strong antifungal property versus the hyphae growth and spore germination of A. versicolor and A. flavus.…”
Section: Pulmonary Aspergillosismentioning
confidence: 99%
“…Statistical analysis of the antifungal activity of the silver nanoparticles was carried out using Statistics for the Social Sciences (SPSS) software, and data are presented as the mean ± standard error of the mean (SE). The ED 50 , ED 95 , and slope of the activity of the nanoparticles against the tested fungi were obtained using probit analysis ( Bahkali et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%